Activated charcoal for oral medicinal purposes: Is it really activated? - Muhammad Abbas AHMAD ZAINI, Nur Atika MOHAMAD (Journal of Applied Pharmaceutical Science, 2015)
No abstract is available.
Keywords: Activated charcoal, oral medicine, pharmaceuticals.